The Influence of Physical Exercise on the Psychological Stress of Women in the Human Resources Management Profession - Yanqiong Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose of this study is to explore the impact of physical exercise on the psychological stress of professional women in the field of human resource management. In order to achieve this goal, a questionnaire survey was used to understand the current physical exercise status of professional women and the level of psychological stress. Through the use of statistical analysis, this paper further analyzes the impact of physical exercise on psychological stress and determines which exercise factors have the greatest impact on psychological stress. The survey results show that the main purpose of most professional women's physical exercise is to entertain and relieve physical and mental pressure, and relatively few people participate in regular exercise. Worryingly, in the survey sample, 44% of professional women are in a state of health risk stress, that is, they bear excessive psychological stress. The study found that the frequency and purpose of physical exercise are two significant factors that affect psychological stress. In particular, taking part in regular physical exercises for 1-2 times/week in a relaxed and happy way can significantly relieve professional women's psychological stress and improve their mental health. This indicates that moderate and regular exercise has a positive effect on reducing the psychological burden on professional women. The results of this study suggest that strengthening regular physical exercise to achieve the effect of physical and mental pleasure is of great significance to reduce the psychological stress of professional women and improve their mental health. Organizations and managers in the field of human resource management can provide better mental health support for professional women by encouraging employees to participate in moderate sports activities. At the same time, these findings also provide a reference for the development of psychological stress intervention measures for professional women, helping them to maintain a positive attitude and efficient working state in their work.